New humanism or post-humanism? Ethical and legal aspects of the legalization of euthanasia in the world in the years 2000-2015 - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2012)
New humanism or post-humanism? Ethical and legal aspects of the legalization of euthanasia in the world in the years 2000-2015 The main aim of this article is to outline the discussion on euthanasia that affects the basic issues of human life – the foundation of human dignity, sense of pain and suffering, conception of the afterlife, quality and value of life, etc. All the indications are that the process of the legalization of euthanasia will develop in the coming decades. Today we need a new paradigm of bioethics, built on the basis of a new humanism which will allow us to adequately analyze such phenomena as death, suffering and dying. The new paradigm of bioethics can be an effective tool in the dispute over the death on request.